2014
DOI: 10.1002/jrs.4455
|View full text |Cite
|
Sign up to set email alerts
|

The detection of copper resinate pigment in works of art: contribution from Raman spectroscopy

Abstract: Copper resinate is a green pigment widely used by the 16th century painters, as many surveys on Italian and European paintings proved. The pigment is a transparent green glaze, and its color is due to copper salts of resin acids. The oldest recipes suggest the preparation of copper resinate by mixing verdigris with terpenic resins as Venice turpentine (conifer resins) on hot ashes. The detection of copper resinate in paintings is up to this time an analytical challenge. We examined the Raman features of copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 38 publications
2
54
0
Order By: Relevance
“…Raman spectroscopy proved successful in identifying these compounds, with some significant differences related to the excitation wavelength used . The best overall results seem to be obtained with a 785‐nm laser (detection of both verdigris and copper resinate, even when mixed with linseed oil) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy proved successful in identifying these compounds, with some significant differences related to the excitation wavelength used . The best overall results seem to be obtained with a 785‐nm laser (detection of both verdigris and copper resinate, even when mixed with linseed oil) …”
Section: Resultsmentioning
confidence: 99%
“…In case OH groups are present, bands appear at 3050–3650 cm −1 . Slightly different band positions and assignments can be found in . Also, the results from the study of the pigments themselves are not straightforwardly applicable to real samples, as the bands of binding media overlap with the organic part of these greens, and binding media alteration because of ageing can also have an effect .…”
Section: Resultsmentioning
confidence: 99%
“…Nastova et al analyzed a green pigment in a medieval Slavonic illuminated manuscript by Raman spectroscopy and SEM‐EDS and concluded that it contained an organo complex of copper, and that further identification of the compound/s was not possible by these techniques . Conti et al acquired Raman and FTIR spectra on two fresh copper resinate commercial samples and on a commercial verdigris, as powders and mixed with linseed oil, using different excitation wavelengths, and reported the analysis of a cross‐section sample removed from a painting by Caravaggio, where they suggest the presence of a copper resinate. These authors state that differentiating between copper resinate and verdigris when mixed with oil becomes complex, and it is expected that this task is even more so in aged samples.…”
Section: Pigmentsmentioning
confidence: 99%
“…Research focused on reconstructing the chemistries of production of traditional pigments following ancient recipes also includes the characterisation of deterioration products [70,79,101,270]. Occasionally, spectra of pigments that have not been previously characterised are still presented in the literature and studied in depth, significantly enriching available libraries [28,55,290].…”
Section: Pigments Inks and Colorantsmentioning
confidence: 99%